A systematic study of Galactic infrared bubbles along the Galactic plane with AKARI and Herschel. II. Spatial distributions of dust components around the bubbles. (28th November 2019) - Hanaoka, Misaki; Kaneda, Hidehiro; Suzuki, Toyoaki; Kokusho, Takuma; Oyabu, Shinki; Ishihara, Daisuke; Kohno, Mikito; Furuta, Takuya; Tsuchikawa, Takuro; Saito, Futoshi
Abstract: Galactic infrared (IR) bubbles, which can be seen as shell-like structures at mid-IR wavelengths, are known to possess massive stars within their shell boundaries. In our previous study (Hanaoka, 2019, PASJ, 71, 6), we expanded the research area to the whole Galactic plane (0^° l 360^° , |b| 5^° ) and studied systematic differences in the shell morphology and the IR luminosity of the IR bubbles between inner and outer Galactic regions. In this study, utilizing high spatial-resolution data of AKARI and WISE in the mid-IR and Herschel in the far-IR, we investigate the spatial distributions of dust components around each IR bubble to discuss the relation between the star-formation activity and the dust properties of the IR bubbles. For the 247 IR bubbles studied in Hanaoka (2019, PASJ, 71, 6), 165 IR bubbles are investigated in this study, which have the Herschel data (|b|1^° ) and known distances. We created their spectral energy distributions on a pixel-by-pixel basis around each IR bubble, and decomposed them with a dust model consisting of polycyclic aromatic hydrocarbons (PAHs), hot dust, warm dust and cold dust. As a result, we find that the offsets of dust heating sources from the shell centers in inner Galactic regions are systematically larger than those in outer Galactic regions. Many of the broken bubbles in inner Galactic regions show large angles between the offset and the direction of the broken shell from the center. Moreover, the spatial variations of the PAH intensity and cold dust emissivity around the IR bubbles in inner Galactic regions are larger than those in outer Galactic regions. We discuss these results in light of the interstellar environments and the formation mechanism of the massive stars associated with the IR bubbles.